The effects of aerobic exercise on 24-hour mean blood glucose levels measured by continuous glucose monitoring in type 2 diabetes: a meta-analysis - Wang, Chou; Tang, Shaokai (Frontiers in Physiology, 2024)
PurposeTo examine the effects of structured aerobic exercise on 24-hour mean blood glucose outcomes assessed by continuous glucose monitors in adults with type 2 diabetes.MethodsThe study established specific inclusion and exclusion criteria and conducted a comprehensive search across five databases, including PubMed, Web of Science, Embase, Cochrane Library, and EBSCOhost from the start year of each database’s coverage to 22 July 2024. The quality of the included studies was evaluated using the Cochrane Handbook 5.1 guidelines. Data analysis was performed using Review Manager 5.4 to determine effect sizes, conduct sensitivity analyses, assess potential biases, and perform subgroup analyses.ResultsA total of 1,034 articles were retrieved, and after 4 rounds of screening, 13 articles were finally selected for meta-analysis. The study included 626 participants (30% female; mean ± SD: age, 59.4 ± 6.4 years; BMI, 29.61 ± 2.24 kg/m2), including 330 in the experimental group and 296 in the control group. The results of the meta-analysis showed that aerobic exercise can improve the 24-hour mean blood glucose in patients with T2DM (d = −0.65, 95% CI: −0.75 to −0.55, p < 0.05). Subgroup analysis showed that moderate-intensity and high-intensity aerobic exercise can improve the 24-hour mean blood glucose in patients with T2DM (d = −0.71, 95% CI: −0.81 to −0.60, p < 0.05), (d = −0.60, 95% CI: −0.98 to −0.22, p < 0.05). Also, 20–40 min and 40–60 min of aerobic exercise per session can improve the 24-hour average blood glucose in patients with T2DM (d = −0.75, 95% CI: −0.91 to −0.59, p < 0.05), (d = −0.59, 95% CI: −0.71 to −0.46, p < 0.05). Aerobic exercise can improve the 24-hour mean blood glucose in patients with T2DM who have a body mass index (BMI) between 29 and 30 kg/m2, as well as those with a BMI greater than 30 kg/m2 (d = −0.65, 95% CI: −0.94 to −0.36, p < 0.05), (d = −0.76, 95% CI: −0.87 to −0.64, p < 0.05).ConclusionAerobic exercise can improve the 24-hour mean blood glucose in patients with T2DM. Additionally, 20–60 min of aerobic exercise with moderate intensity, and high intensity can improve the 24-hour mean blood glucose in patients with T2DM who have a BMI greater than 29 kg/m2.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifer PROSPERO CRD42024590812